Structural, depositional and geochemical studies on Quaternary travertine occurances along strike slip faults: A case study from East Anatolian Fault System (EAFS), Elazi?, Turkey - Çolak, Serap; Özkul, Mehmet; Aksoy, Ercan (My University, 2011)
[Abstract Not Available]
Keywords: East Anatolian fault system; Elazi?; Strike slip fault; Travertine